Molecularly imprinted polymer solid phase extraction for the analysis of organophosphorus pesticides in food samples - Salleh, Syairah (2012)
A new material based on molecularly imprinted polymers (MIP) was prepared as solid phase extraction (SPE) sorbent for sample enrichment in the analysis of organophosphorus pesticides (OPPs). The polymer with binding sites situated on the surface shows many advantages including high selectivity and high recoveries towards the target analytes. The MIP was synthesized by non-covalent imprinting technique using quinalphos as the template molecule, methacrylic acid (MAA) as functional monomer, ethylene glycol dimethacrylate (EGDMA) as crosslinker and acetonitrile as porogen solvent. The physical characteristics of the MIP were characterized using fourier transform infrared spectrometry (FTIR), CHN analyzer, field emission scanning electron microscopy (FE-SEM), nitrogen adsorption and UV-VIS spectrometry. The three OPPs (diazinon, quinalphos and chlorpyrifos) were selected as target analytes as they are widely used in agriculture sector. Various parameters and conditions affecting the extraction efficiency of the imprinted polymers were evaluated to optimize the selective preconcentration of OPPs compounds from aqueous samples. By using 100 mg of sorbent, it was found that the optimum MIP-SPE conditions were: 10 mL loading sample volume, 30% of acetonitrile in water as washing solvent, 5% acetic acid in methanol as elution solvent, and 6 mL elution solvent volume. The extracts were analyzed by high performance liquid chromatography coupled with ultraviolet-visible detection at 200 nm. The accuracy and selectivity of the MIP-SPE method developed were verified with non-imprinted polymer solid phase extraction (NIP-SPE) and commercial C18-SPE for comparison. The MIP-SPE showed superior extraction efficiency towards the three selected OPPs compared to the NIP-SPE and commercial C18-SPE. The limits of detection (LOD) of OPPs for MIP-SPE ranged from 0.83 µg L-1-2.8 µg L-1 with the percentage recovery of greater than 91%. Meanwhile, the LODs of OPPs for NIP-SPE and C18-SPE were in the range of 3.77 µg L-1-6.14 µg L-1 and 2.87 µg L-1-3.12 µg L-1, respectively and percentage recoveries of greater than 62% and 88%, respectively. The developed method was successfully applied to the analysis of OPPs in two selected fruit samples namely, grapes and green apples. The analysis of OPPs in samples using the developed MIP-SPE showed good results with recoveries of 89.74%-99.70% and RSDs of less than 3%.